Uso de 5 dosis de (nicotiana glauca) para el control de Mosca de la fruta (anastrepha fraterculus), en el cultivo de durazno (prunus persica) en chiquicha, Pelileo, Tungurahua. 2021. - Morales Carrasco, Paúl Andrés (2022)
This research study was carried out to evaluate the effect of a bioinsecticide based on false tobacco dosed at 20%, 15%, 10%, 5% and trial to control fruit flies in peach trees in the Pachanlica sector, located in the Chiquicha Parish belonging to the Tungurahua Province. The project's methodology consisted of detecting the specific pest (genus- species) of fruit flies affecting peach production using a system of "Harris" traps for home monitoring using sugarcane juice at a bait rate of 0.5l/trap every 15 days. Jackson traps (TJ) were also used for monitoring and detection of fruit flies, which, based on data processing with the flytrap day formula (MTD), yielded results of 0.17 for T0 being the trap with the highest captures in control, for T1 with 0.05 for T2 with 0.14 for T3 with 0.11 and T4 with 0.9 of the average. The statistical results of the rearing of controlled flies were 0.001 for the variable dose of false tobacco and for the linear effect of the functional analysis <0.0001, being both highly significant for these sectors, in addition to a Tukey test at 5%, where the significant ranges were the doses of 20% (A), and 15% (B), for treatments four and three being effective against fly control for infection in peach fruits. The coefficient of variation of the experiment was 29.30%, establishing that the doses of Nicotiana glauca extract control Anastrepha fraterculus infection under field conditions is effective in repelling fruit fly attack during the phenological stages of production.